2015
DOI: 10.1021/acsphotonics.5b00143
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Ultrafast Photoluminescence of Colloidal Silicon Nanocrystals with Changing Surface Chemistry

Abstract: The role of surface species in the optical properties of silicon nanocrystals (SiNCs) is the subject of intense debate. Changes in photoluminescence (PL) energy following hydrosilylation of SiNCs with alkyl-terminated surfaces are most often ascribed to enhanced quantum confinement in the smaller cores of oxidized NCs or to oxygen-induced defect emission. We have investigated the PL properties of alkyl-functionalized SiNCs prepared using two related methods: thermal and photochemical hydrosilylation. Photochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 85 publications
5
63
1
3
Order By: Relevance
“…Hydrosilylation involves the addition of aS i ÀHb ond across multiple CÀCb onds and is typically facilitated by exposure to heat, [30] light, [31] radical initiators, [32] transitionmetal catalysts, [33] Lewis acids, [34] or plasmons. [35] Thermally initiated hydrosilylation is widely employed;i tp roceeds independent of particle size and shape,d oes not require ac atalyst that could contaminate the product and compromise target properties,a nd provides efficient surface coverage.T he generally accepted mechanism for this reaction involves the thermally initiated homolytic cleavage of surface Si À Hbonds to provide surface silyl radicals that subsequently react with terminal carbon-carbon multiple bonds.W hile af ew rare exceptions exist, [36] reactions of this type are typically performed in neat alkene/alkyne and until recently it has long been assumed that they yielded surface-bonded monolayers.I n2 014, Yang et al conclusively demonstrated that typical thermal hydrosilylation conditions induce ligand oligomerization and that the degree of oligomerization increases with oxygen content, reaction temperature,a nd ligand concentration.…”
Section: Hydrosilylation Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrosilylation involves the addition of aS i ÀHb ond across multiple CÀCb onds and is typically facilitated by exposure to heat, [30] light, [31] radical initiators, [32] transitionmetal catalysts, [33] Lewis acids, [34] or plasmons. [35] Thermally initiated hydrosilylation is widely employed;i tp roceeds independent of particle size and shape,d oes not require ac atalyst that could contaminate the product and compromise target properties,a nd provides efficient surface coverage.T he generally accepted mechanism for this reaction involves the thermally initiated homolytic cleavage of surface Si À Hbonds to provide surface silyl radicals that subsequently react with terminal carbon-carbon multiple bonds.W hile af ew rare exceptions exist, [36] reactions of this type are typically performed in neat alkene/alkyne and until recently it has long been assumed that they yielded surface-bonded monolayers.I n2 014, Yang et al conclusively demonstrated that typical thermal hydrosilylation conditions induce ligand oligomerization and that the degree of oligomerization increases with oxygen content, reaction temperature,a nd ligand concentration.…”
Section: Hydrosilylation Reactionsmentioning
confidence: 99%
“…[40] Perfluorodecyl groups were grafted onto Si-NC surfaces upon heating in am icrowave reactor (Scheme 2). [43] Other room-temperature hydrosilylation routes make use of transition-metal catalysts,b ut these additives can compromise Si-NC properties (e.g., PL quenching) and removing the residual catalyst is difficult. [41] While avery small number of exceptions exist, [42] thermal hydrosilylation requires high reaction temperatures,a nd as ar esult only high-boiling alkenes and alkynes can be conveniently grafted onto Si-NC surfaces.P hotochemically induced hydrosilylation provides as eemingly obvious alternative.H owever,i ts utility is limited by size-dependent reactivity,i ntolerance to chemical functionality,a nd long reaction times.…”
Section: Hydrosilylation Reactionsmentioning
confidence: 99%
“…Like the AP material, PEGylated SiNCs exhibit both 'fast' and 'slow' PL relaxation (Fig. 1b), where the fast (ns) relaxation has been linked to surface states [64] while the PL quantum yield is dominated by the slow (µs) mode [65,66]. Here, the fast decay is around 4 ns independent of sample, with a slow decay of around 10 µs.…”
Section: Resultsmentioning
confidence: 95%
“…Hydrosilylierung beschreibt die Addition einer Si-HBindung an C-C-Mehrfachbindungen und wird typischerweise durch Einsatz von Wärme, [30] Licht, [31] Radikalinitiatoren, [32] Übergangsmetallkatalysatoren, [33] Lewis-Säuren [34] oder Plasmonen [35] [37] Unter Verwendung von NALDI-Massenspektrometrie (nanostructure-assisted laser desorption/ ionization) wurden Dodecen-Oligomere mit bis zu 7W iederholungseinheiten auf der SiNK-Oberfläche gefunden (Abbildung 1a). In Übereinstimmung mit diesem Bericht verçffentlichten Panthani et al Tr ansmissionselektronenmikroskopie(TEM)-Abbildungen von Alkyl-stabilisierten SiNanokristallen, die mittels thermischer Hydrosilylierung erhalten wurden.…”
Section: Hydrosilylierungunclassified
“…Daneben existiert die photochemische Hydrosilylierung als Alternative,d eren Einsatzfähigkeit allerdings durch grçßenabhängige Reaktivität der SiNKs,I ntoleranz gegenüber funktionellen Gruppen, wie auch die bençtigten langen Reaktionszeiten limitiert ist. [43] Wied ie photochemische Reaktion verläuft die Über-gangsmetall-katalysierte Hydrosilylierung bei Raumtemperatur.U nglücklicherweise gehen damit Probleme einher, sodass Verunreinigungen und Katalysatorreste schlecht abgetrennt werden kçnnen und die Eigenschaften der Nanokristalle negativ beeinflusst werden. [44] Aufgrund dessen wurden neue Methoden bençtigt, die eine Funktionalisierung Abbildung 1. a) NALDI-Massenspektren von SiNKs funktionalisiert bei unterschiedlichen Temperaturen.…”
Section: Hydrosilylierungunclassified